Cost of venous thromboembolism in hospitalized medically ill patients. - Pendergraft, Trudy; Atwood, Mark; Xianchen Liu; Phatak, Hemant; Liu, Larry Z.; Oster, Gerry (American Journal of Health-System Pharmacy, 2013)
Purpose. The results of a study to estimate the economic costs of venous thromboembolism (VTE) in hospitalized nonsurgical patients during initial admissions and subsequent to hospital discharge are presented. Methods. Using a database linking admission records from more than 150 U.S. hospitals to health insurance claims, 49,948 patients 40 years of age or older who were hospitalized at least once during a 6-year period for diagnoses other than VTE or traumatic injury and who met other inclusion criteria were identified. Costs were tallied from the index admission to postdischarge day 180 for patients with and patients without evidence of VTE. Ordinary least-squares regression was used to estimate the independent relationship between VTE and total health care costs, controlling for differences in patient characteristics. Results. Two hundred forty-two patients (0.5%) had VTE during the index admission, 317 (0.6%) had VTE after the index admission discharge; in total, 559 (1.1%) had VTE through postdischarge day 180. Among the 242 patients with VTE during their index admission, the adjusted mean total health care costs over 180 days were $17,848 higher than among those without VTE ($47,416 versus $29,568, p < 0.001); for the 317 patients with postdischarge VTE, the adjusted mean total 180-day costs were $51,863 higher than for those without postdischarge VTE ($74,136 versus $22,273, p < 0.001). Conclusion. Among medically ill patients admitted to the hospital, health care costs were significantly higher among those who developed VTE during hospitalization or after discharge compared with those who did not develop VTE.